2022
DOI: 10.1108/bjm-07-2021-0278
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the link between learning from error climate and professionals' engagement in social learning activities after errors

Abstract: PurposeLearning from errors is a complex process that requires careful support. Building on affective events theory, the purpose of this paper is to explore how a supportive learning from error climate can contribute to social learning from errors through affective and cognitive error responses by individual professionals.Design/methodology/approachA total of 139 early-career auditors completed an online questionnaire consisting of validated survey scales, allowing for serial mediation analysis to compare dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 60 publications
6
7
0
Order By: Relevance
“…Second, we hypothesize that auditors will report less error learning from routine (compared to non-routine) errors (in line with Embrey, 2005;Zhang et al, 2019), as these errors are easily attributable to inattention or coincidence, rather than a lack of knowledge (Sutcliffe and Rugg, 1998). Third, we hypothesize that auditors will learn less from errors when they experience strong (rather than weak) negative emotions, as these emotions take up crucial cognitive resources needed for learning, and may inhibit error learning (in line with, i.e., Heimbeck et al, 2003;Zhao et al, 2019;Smeets et al, 2022). Finally, we expect that auditors will report less error learning with high (rather than low) time pressure, as they are likely to prioritize urgent tasks over learning, and because the error's cause can be externalized (in line with, i.e., Zhao and Olivera, 2006;Homsma et al, 2009;Putz et al, 2012).…”
Section: Introductionsupporting
confidence: 52%
See 4 more Smart Citations
“…Second, we hypothesize that auditors will report less error learning from routine (compared to non-routine) errors (in line with Embrey, 2005;Zhang et al, 2019), as these errors are easily attributable to inattention or coincidence, rather than a lack of knowledge (Sutcliffe and Rugg, 1998). Third, we hypothesize that auditors will learn less from errors when they experience strong (rather than weak) negative emotions, as these emotions take up crucial cognitive resources needed for learning, and may inhibit error learning (in line with, i.e., Heimbeck et al, 2003;Zhao et al, 2019;Smeets et al, 2022). Finally, we expect that auditors will report less error learning with high (rather than low) time pressure, as they are likely to prioritize urgent tasks over learning, and because the error's cause can be externalized (in line with, i.e., Zhao and Olivera, 2006;Homsma et al, 2009;Putz et al, 2012).…”
Section: Introductionsupporting
confidence: 52%
“…First, experiencing these emotions may cause professionals to withdraw from the situation, missing out on important learning opportunities (Zhao et al, 2019). Second, these emotions occupy a person's working memory, limiting the information processing that is essential for leaning (Zhao, 2011;Tulis et al, 2016;Smeets et al, 2022). Literature on emotional regulation has shown that individuals prioritize relieving strong emotions over problem-solving and learning, with the consequence that strong negative emotions may inhibit error learning (Kanfer and Ackerman, 1989;Ilgen and Davis, 2000;Tulis et al, 2016;Hökkä et al, 2020).…”
Section: Strong Negative Emotionsmentioning
confidence: 99%
See 3 more Smart Citations